Timeline of antibiotics prophylaxis and incidence of surgical site infections in patients of caesarean section at public sector hospital Karachi - Ismail, Shumaila; Khowaja, Danish; Dhiloo, Azizullah Khan; Shamim Haque; Riffat Jaleel; Memon, Sughand Umer (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the effect of the timing of antibiotic prophylaxis on the incidence of surgical site infections in patients undergoing caesarean section in a public-sector tertiary care setting. Method: The prospective study was conducted at Gynaecology Unit 2 of the Dr Ruth KM Pfau Civil Hospital, Karachi, from November 2023 to April 2024, and comprised adult inpatients aged 18-45 years who had elective or emergency caesarean section. The patients were divided into four groups based on the timing of antibiotic administration; group A <30 minutes, group B 30-60 minutes, group C 60-120 minutes, and group D >120 minutes. All the patients received a single dose of prophylactic antibiotic in the shape pf 2g injection of ceftriaxone. Following hospital discharge, the patients were monitored for wound infection for 30 days. Data was analysed using SPSS 21. Results: Of the 323 patients with mean age 33.88±6.61 years, 81(25.07%) were in group A with mean age 34.58±6.22 years, 81(25.07%) were in group B with mean age 33.50±6.81 years, 81(25.07%) were in group C with mean age 33.09±6.85 years, and 80(24.76%) were in group D with mean age 35.32±6.33 years. Overall, 36(11.1%) patients developed wound infection; 4(11.1%), 5(13.9%), 12(33.3%) and 15(41.7%) in group A, B, C and D, respectively (p=0.010). Conclusion: The timing of prophylactic antibiotic administration was found to have significantly affected the occurrence of surgical site infections. Key Words: Antibiotics, Surgical site infections, Caesarean section, Prophylaxis.